The influence of family accommodation on pediatric hospital experience in Canada - Linda S. Franck; Deron Ferguson; Sarah Fryda; Nicole Rubin (BMC, 2017)
Abstract Background The goals of our study were to describe the types of family accommodation for parents of hospitalized children and to examine their influence on the pediatric hospital experience. Methods This multi-site cohort survey included 10 hospitals in Ontario Province, Canada. Participants were parents of inpatient children (n = 1240). Main outcome measures included ratings of three parent-reported measures of hospital experience: overall hospital experience; willingness to recommend the hospital to family or friends; and how much the accommodation type helped parent stay involved in their child's hospital care. Results Parents most often stayed in the child's room (74.7%), their own home (12.3%), hotel (4.0%) or a Ronald McDonald House (3.0%). Accommodation varied based on hospital, parent and child factors. Length of stay and the child's health status were significant predictors for overall hospital experience and recommending the hospital to family or friends, but accommodation type was not. Families who stayed at a Ronald McDonald House reported greater involvement in their child's care compared with other accommodation types (odds ratio: 1.54-20.73 for contrasted accommodation types). Conclusion Use of different overnight accommodations for families of hospitalized pediatric patients in Canada is similar to a previous report of U.S. family hospital accommodations. In contrast to the previous U.S. findings, Canadian hospital experience scores were lower and accommodation type was not a significant predictor of overall hospital experience or willingness to recommend the hospital. In Canada, as in the U.S., families who stayed at a Ronald McDonald House reported that this accommodation type significantly improved their ability to be involved in their child's care.